Konsep Adil dan Ihsan dalam Transaksi Ekonomi menurut Imam Al-Ghazali dan Pengaruh Tasawuf Terhadapnya (Studi Analisis Terhadap Kitab Ihya’ al-‘Ulum al-Din) - Syamsuri Syamsuri; Muhammad Ridwan (Universitas Darussalam Gontor, 2019)
There are many fraudulent economic transactions happened in everyday life, the main factor for this situation because the people is far away from the religiosity values. For this reality, Imam al-Ghazali's economic concepts can be one solution to improve it, because the concept he offers is full of the values of religiosity through his Sufism approach. The concept is becoming ‘adl ( fair) and Ihsan in every economic transactions. Among his ideas in these two concepts is the obligation to apply justice in economic transactions, because justice in the business world (al-Tijārah) is like happiness, which is a profit. The prohibition on hoarding goods (al-Ihtikār), the use of counterfeit money in transactions (Tarwīj al-Zayf min al-Darāhim fī Atsna al-Naqd), manipulation of goods prices (Ghabn) and several other ideas. Based on this and also because of the lack of studies of his thoughts in the economic sphere with his Sufism approach, the study of ideas becomes very interesting to study and develop in an effort to correct the deviations of economic transactions among the community.